The Influence of Promotions and Prices on Purchasing Decisions at Kagumi Kopi Nusantara Cicurug Sukabumi - Juniar, Nadia; Andari, Titiek Tjahja; Samsuri (International Journal of Management and Business Intelligence, 2024)
This research aims to analyze and identify the influence of promotions and prices, both simultaneously and partially, on purchasing decisions for Kagumi Kopi Nusantara. Questionnaires were distributed to 100 respondents taken using a purposive sampling technique with the criteria; consumers have purchased Kagumi Kopi Nusantara products at least 2 times and consumers are seen as mature enough to fill out the questionnaire, at least 17 years old. The questionnaire was tested using validity tests, reliability tests and classical assumption tests. The test results are valid, reliable, and can be used for regression data. The analytical method used in this research is descriptive and verification methods. The research results show that the promotion and price variables, both simultaneously and partially, have a positive and significant effect on purchasing decisions for Kagumi Kopi Nusantara. The test results for the coefficient of determination (R Square) were 52.8% while the remaining 47.2%. The relationship between promotion and price is very strong with a correlation coefficient of 0.727.